Ustekinumab versus adalimumab for induction and maintenance therapy in biologic-naive patients with moderately to severely active Crohn's disease: a multicentre, randomised, double-blind, parallel-group, phase 3b trial. Issue 10342 (11th June 2022) - Sands, Bruce E; Irving, Peter M; Hoops, Timothy; Izanec, James L; Gao, Long-Long; Gasink, Christopher; Greenspan, Andrew; Allez, Matthieu; Danese, Silvio; Hanauer, Stephen B; Jairath, Vipul; Kuehbacher, Tanja; et al.
Summary: Background: Active-comparator trials are important to inform patient and physician choice. We aimed to evaluate the efficacy and safety of monotherapy with either ustekinumab or adalimumab in biologic-naive patients with moderately to severely active Crohn's disease. Methods: We conducted a randomised, double-blind, parallel-group, active-comparator, phase 3b trial (SEAVUE) at 121 hospitals or private practices in 18 countries. We included biologic-naive patients aged 18 years or older with moderately to severely active Crohn's disease and a Crohn's Disease Activity Index (CDAI) score of 220–450, who had not responded to or were intolerant to conventional therapy (or were corticosteroid dependent) and had at least one ulcer of any size at baseline endoscopic evaluation. Eligible patients were randomly assigned (1:1; via an interactive web response system) to receive ustekinumab (approximately 6 mg/kg intravenously on day 0, then 90 mg subcutaneously once every 8 weeks) or adalimumab (160 mg on day 0, 80 mg at 2 weeks, then 40 mg once every 2 weeks, subcutaneously) through week 56. Study treatments were administered as monotherapy and without dose modifications. Patients, investigators, and study site personnel were masked to treatment group assignment. The primary endpoint was the proportion of patients who were in clinical remission (CDAI score <150) at week 52 in the intention-to-treat population (ie, all patients who were randomly assigned to a treatment group). This trial is registered with ClinicalTrials.gov, NCT03464136, and EudraCT, 2017-004209-41. Findings: Between June 28, 2018, and Dec 12, 2019, 633 patients were assessed for eligibility and 386 were enrolled and randomly assigned to receive ustekinumab (n=191) or adalimumab (n=195). 29 (15%) of 191 patients in the ustekinumab group and 46 (24%) of 195 in the adalimumab group discontinued study treatment before week 52. There was no significant difference between the ustekinumab and adalimumab groups in the occurrence of the primary endpoint; at week 52, 124 (65%) of 191 patients in the ustekinumab group versus 119 (61%) of 195 in the adalimumab group were in clinical remission (between-group difference 4%, 95% CI –6 to 14; p=0·42). Safety for both groups was consistent with previous reports. Serious infections were reported in four (2%) of 191 patients in the ustekinumab group and five (3%) of 195 in the adalimumab group. No deaths occurred through week 52 of the study. Interpretation: Both ustekinumab and adalimumab monotherapies were highly effective in this population of biologic-naive patients, with no difference in the primary outcome between the drugs. Funding: Janssen Scientific Affairs.